88 C-REACTIVE PROTEIN DOWN-REGULATES INTERLEUKIN-10 SECRETION FROM HUMAN MONOCYTE-DERIVED MACROPHAGES VIA INHIBITION OF PROTEIN KINASE A. (1st January 2006) - Singh, U.; Ciobanu, D.; Devaraj, S.; Jialal, I.
Abstract : Inflammation is pivotal in atherogenesis. C-reactive protein (CRP) contributes to atherosclerosis and is present in the atherosclerotic lesions. Among anti-inflammatory cytokines, IL-10 produced by Th2 cells and macrophages plays a protective role in atherosclerosis. IL-10-deficient mice develop increased atherosclerosis and gene transfer of IL-10 reduces atherosclerosis. Macrophages present in human atherosclerotic lesions express IL-10. Thus we tested the effect of CRP on IL-10 secretion in human monocyte-derived macrophages (HMDMs). CRP preparation used had minimal endotoxin and no azide contamination. HMDMs were treated with CRP (25 μg/mL/12 hrs) and activated with 0.5 μg/mL of lipopolysacharide (LPS), which signals through toll-like receptors (TLR-4) and are pathogenically related to atherosclerosis. The effect of CRP on IL-10 was studied at protein (IL-10 measurement in culture medium by ELISA and intracellular IL-10 by flow cytometry) and at mRNA levels (by real-time RT-PCR). CRP inhibited IL-10 secretion ( p < .01) and intracellular IL-10 (p < .01). CRP also inhibited IL-10 mRNA levels (p < .001) and decreased mRNA stability (p < .01). To ensure effects due to CRP per se, native CRP was boiled and preabsorbed to anti-CRP- IgG coated plate that failed to affect LPS induced IL-10 secretion unlike native CRP. IL-10 is regulated by cyclic adenosine monophosphate (cAMP)/protein kinase A (PKA) system. To get mechanistic insights, we measured cAMP levels that showed decreased release (p < .01) with CRP treatment. Furthermore, pretreatment of cells with cAMP agonists resulted in significant reversal (p < .001) of CRP effect on IL-10 secretion. CRP also decreased (p < .05) levels of phospho-CREB (cAMP response element binding protein, which gets phosphorylated upon activation) as measured by ELISA and Western blot. Hence, we show that CRP inhibits IL-10 secretion via down-regulation of cAMP/PKA system. CRP acts through Fcγ receptor pathways. The blocking antibodies to CD64 (Fcγ RI) and CD32 (Fcγ RII) and not CD16 (Fcγ RIII) attenuated CRP mediated effects. In vivo administration of human CRP (20 mg/kg bw for 3 days) to Sprague-Dawley rats (n = 6) resulted in a significant decrease (p < .05) in serum IL-10 levels as compared to control rats. Thus, we show that in vitro and in vivo, CRP inhibited IL-10 levels. To conclude, our data suggest a proinflammatory effect of CRP, that is, inhibition of the critical anti-inflammatory cytokine (IL-10) synthesis, which could have major implications in atherogenesis.